The effect of coffee on blood pressure and cardiovascular disease in hypertensive individuals: a systematic review and meta-analysis - Mesas, Arthur Eumann; Leon-Muñoz, Luz M; Rodriguez-Artalejo, Fernando; Lopez-Garcia, Esther (The American journal of clinical nutrition, 2011)
The effect of coffee and caffeine on blood pressure (BP) and cardiovascular disease (CVD) in hypertensive persons is uncertain. The objective was to summarize the evidence on the acute and longer-term effects of caffeine and coffee intake on BP and on the association between habitual coffee consumption and risk of CVD in hypertensive individuals. A systematic review and meta-analysis of publications identified in a PubMed and EMBASE search up to 30 April 2011 was undertaken. Data were extracted from controlled trials on the effect of caffeine or coffee intake on BP change and from cohort studies on the association between habitual coffee consumption and CVD. In 5 trials, the administration of 200-300 mg caffeine produced a mean increase of 8.1 mm Hg (95% CI: 5.7, 10.6 mm Hg) in systolic BP and of 5.7 mm Hg (95% CI: 4.1, 7.4 mm Hg) in diastolic BP. The increase in BP was observed in the first hour after caffeine intake and lasted ≥3 h. In 3 studies of the longer-term effect (2 wk) of coffee, no increase in BP was observed after coffee was compared with a caffeine-free diet or was compared with decaffeinated coffee. Last, 7 cohort studies found no evidence of an association between habitual coffee consumption and a higher risk of CVD. In hypertensive individuals, caffeine intake produces an acute increase in BP for ≥3 h. However, current evidence does not support an association between longer-term coffee consumption and increased BP or between habitual coffee consumption and an increased risk of CVD in hypertensive subjects.